2017
DOI: 10.12659/msm.902025
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Platelet-Rich Plasma with Whole Blood Harvested Intraoperatively During Spinal Fusion

Abstract: BackgroundPlatelet-rich plasma (PRP) has gained growing popularity in use in spinal fusion procedures in the last decade. Substantial intraoperative blood loss is frequently accompanied with spinal fusion, and it is unknown whether blood harvested intraoperatively qualifies for PRP preparation.Material/MethodsWhole blood was harvested intraoperatively and venous blood was collected by venipuncture. Then, we investigated the platelet concentrations in whole blood and PRP, the concentration of growth factors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results of multivariate analysis showed that SLIC score (more than 7.5) could be a risk factor for poor prognosis of cervical SCI with subaxial cervical fracture-dislocation after surgical treatment, because the degree of the cervical SCI aggravates as the SLIC score increases, which indicates poor fracture morphology, severe cervical nerve injury, or SLC complex injury. Full functional recovery of the cervical spinal cord is hard to achieve for patients with a degree of spinal cord compression more than 50% in the acute injury mode [ 27 29 ]. Our study showed that MSCC of more than 55.8% can result in poor prognosis of cervical SCI with inferior cervical fracture-dislocation after surgical treatment, and our results are consistent with previous studies and could also be helpful for the spinal surgeon in deciding on the optimal operation time.…”
Section: Discussionmentioning
confidence: 99%
“…The results of multivariate analysis showed that SLIC score (more than 7.5) could be a risk factor for poor prognosis of cervical SCI with subaxial cervical fracture-dislocation after surgical treatment, because the degree of the cervical SCI aggravates as the SLIC score increases, which indicates poor fracture morphology, severe cervical nerve injury, or SLC complex injury. Full functional recovery of the cervical spinal cord is hard to achieve for patients with a degree of spinal cord compression more than 50% in the acute injury mode [ 27 29 ]. Our study showed that MSCC of more than 55.8% can result in poor prognosis of cervical SCI with inferior cervical fracture-dislocation after surgical treatment, and our results are consistent with previous studies and could also be helpful for the spinal surgeon in deciding on the optimal operation time.…”
Section: Discussionmentioning
confidence: 99%